2017
DOI: 10.1021/acs.organomet.7b00465
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Electron-Deficient Triruthenium Hydrido Complex Having a Bridging Carbonyl Ligand: Influence of a CO Ligand on the Properties and Reactivities of a Hydrido Cluster

Abstract: A novel triruthenium hydrido cluster, (Cp*Ru)3(μ3-H)­(μ-H)2(μ-CO) (4; Cp* = η5-C5Me5), having a bridging CO ligand was synthesized by the reaction of {Cp*Ru­(μ-H)}3(μ3-O) (3) with methanol. Upon introduction of a CO ligand, the cyclic voltammogram of 4 demonstrated a significant shift of the redox potential in the positive direction in comparison to a pentahydrido complex, {Cp*Ru­(μ-H)}3(μ3-H)2 (1), which adopts the same 44-electron configuration. Owing to its coordinatively unsaturated nature, 4 readily react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…Although the formal oxidation state of the Ru 3 centers in 3a is lower than that in 6, the E 1/2 0/+ value shifted in the positive direction relative to that of 6 (E 1/2 0/+ = −731 mV, E p,a 0/+ = −673 mV). 46 This result suggests that the HOMO of 3a was substantially stabilized upon the introduction of a p-cymene group, despite its lower formal oxidation state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the formal oxidation state of the Ru 3 centers in 3a is lower than that in 6, the E 1/2 0/+ value shifted in the positive direction relative to that of 6 (E 1/2 0/+ = −731 mV, E p,a 0/+ = −673 mV). 46 This result suggests that the HOMO of 3a was substantially stabilized upon the introduction of a p-cymene group, despite its lower formal oxidation state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Treatment of 3a with 1 atm of D 2 at 25 °C resulted in 50% deuteration at the Ru−H site after 3 h. Although the H/D exchange rate was considerably lower than that of 6 (100% deuteration in 3 h at 25 °C), it was comparable to that of [(Cp*Ru) 3 (μ-H) 2 (μ 3 -H)(μ-CO)]. 46 Thermolysis of 3a in C 6 D 6 also led to the deuteration of hydrides, although the reaction proceeded sluggishly. The Ru− H site was only 10% deuterated after 48 h at 80 °C, while the hydrides in 6 were converted by 73% after 40 h at 80 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The C(2)–C(3) distance of 1.42 Å in the optimized DFT structure is typical for μ 3 -η 2 -alkyne ligands parallel to one of the M–M edges of a M 3 triangle. , The optimized C(4)–C(5) distance (1.331 Å) is considerably shorter than the C–C bond length of the μ 3 -η 2 -CCH 2 ligand in [(Cp*Ru) 3 (μ 3 -η 2 -CCH 2 )­(μ-H)­(μ-CO)] ( 7 ; 1.389(8) Å), probably due to the absence of π coordination.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of π coordination also causes a remarkable downfield shift of the 13 C signal of the C β atom in 4 (δ 101.7) in comparison to those of the μ 3 -η 2 -CCH 2 ligands in 5 (δ 70.1), 20 [(Cp*Ru) 3 (μ 3 -η 2 -n PrCCH)(μ 3 -η 2 -CCH 2 )(μ-H)] (6; δ 68.9), 26 and 7 (δ 56.9) (Table 2). 16 Although the C α signal in 4 (δ 261.6) was located considerably more upfield than those of the μ 3 -η 2 -vinylidene complexes 5−7 (δ 306.4− 296.6), its chemical shift is similar to those of the reported triruthenium μ-vinylidene complex [Ru 3 (μ-CCH 2 )(μ 3 -κ 2 -HNNMe 2 )(μ 3 -η 2 -HCCH)(CO) 7 ] (δ 248.4) 21 and diruthenium μ-vinylidene complex [{CpRu(CO)} 2 (μ-CCH 2 )(μ-CO)] (δ 240.1). 27 Takemoto et al demonstrated that the reaction of [(Cp*Ru) 2 (μ-CH)(μ-NPh)] + with KN(SiMe 3 ) 2 resulted in the formation of a μ-carbido complex via the exclusive deprotonation of the μ-methylidyne ligand.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation